Sales Training Effectiveness: A Review - Das, Komal K.; Upadhyay, Ashwani Kumar; Das, Subrata (Prabandhan: Indian Journal of Management, 2013)
The current market situation is twofold - organizations are coping with the present marketplace scenario of globalization, tough competition, technology, and changing demographics, whereas salespeople face sophisticated and knowledgeable customers, impinging enormous pressure to perform at levels never seen and faced before. Sustainability through skilled sales force serves as a primary rationale for organizations to invest in sales training. Thus, sales organizations now emphasize on competencies and commitment for continual learning apart from task-related knowledge, skills, and abilities, which are now required, expected, and demanded from all the workforce. These aspects are likely to bring significant changes in the strategic approach towards sales training content, learning, and methodology. This paper aims to build a narrative literature review in relation to sales force training evaluation and effectiveness published between 1982-2012. The present paper examines the emergence and impact of competencies, methodologies, transfer of learning on training effectiveness over a period. Several research gaps were identified, especially in the areas of performance improvement for managers as well as the factors affecting learning adoption, content, and trainees' perceptions. The paper closes with some observations on sales training effectiveness aspects, with emphasis on efficiency and several specific areas of further research were identified. The study provides a clearer view of major issues related to the field of sales training effectiveness for business organizations, policy makers, practitioners, researchers, and academicians.